2020
DOI: 10.3390/genes11111283
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing in the Diagnosis of Patients with Bardet–Biedl Syndrome—New Variants and Relationship with Hyperglycemia and Insulin Resistance

Abstract: Bardet-Biedl syndrome (BBS) is a rare autosomal recessively inherited disease with major clinical symptoms such as: obesity, retinal degeneration, polydactyly and renal abnormalities. The aim of the study was to assess the spectrum of gene variants among patients with BBS, identified on the basis of nationwide genetic studies of monogenic diabetes in Polish population. Out of 575 patients enrolled for genetic testing from February 2017 to July 2019, 25 patients with a clinical suspicion of BBS were selected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Many of the studies investigating glycaemia and diabetes mellitus in BBS have been in very small samples, which has led to inconsistent results between studies. In a study of 10 participants with BBS mainly with disease-causing variants in BBS9 and BBS10, strong associations were observed between hyperglycaemia and insulin resistance in participants with disease-causing variants in BBS9 [6]. This contrasts with earlier work including a small cohort study of 16 adults with BBS that found the majority were not glucose intolerant and had normal insulin resistance [7].…”
Section: Glycaemia and Diabetes Mellitus In Bardet Biedl Syndromementioning
confidence: 72%
“…Many of the studies investigating glycaemia and diabetes mellitus in BBS have been in very small samples, which has led to inconsistent results between studies. In a study of 10 participants with BBS mainly with disease-causing variants in BBS9 and BBS10, strong associations were observed between hyperglycaemia and insulin resistance in participants with disease-causing variants in BBS9 [6]. This contrasts with earlier work including a small cohort study of 16 adults with BBS that found the majority were not glucose intolerant and had normal insulin resistance [7].…”
Section: Glycaemia and Diabetes Mellitus In Bardet Biedl Syndromementioning
confidence: 72%
“…Nowadays, NGS is the technology of choice for the study of BBS [23][24][25] . It allows the identification of new causative variants and further reanalysis to assess new BBS genes that may have been identified after a primary analysis or had not been covered by any of the classical methods initially used 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients provided written informed consent for participation in the study. The diagnosis of ALMS or BBS syndrome was confirmed in patients by sequencing the related genes, as previously described [ 25 , 26 ]. Urine samples were collected from three patients with genetically confirmed ALMS syndrome (with pathogenic variants: NM_001378454.1:c.8161C>T(;)11204C>A, NM_001378454.1:c.4108dup(;)7373_7376del and NM_001378454.1:c.1900C>T(;)11877_11878del in ALMS1 and MIM No.…”
Section: Methodsmentioning
confidence: 99%